Streptococcus bovis isolado ou combinado com farelo de trigo como aditivo para ensilagem de capim-tanzânia - Bonelli, Emerson Alencar (2011)
The present aim of this experiment was to evaluate the development of microbial populations, fermentation, gas and effluent losses, as well as the recovery of dry matter and crude protein, chemical composition and degradability in situ of Tanzania grass silage inoculated with Streptococcus bovis associated or not with wheat meal. The experimental delineation was completely randomized with six treatments and six replications: Tanzania grass silage (control); Tanzania grass silage inoculated with 10% wheat meal; Tanzania grass silage inoculated with 106 ufc/g Streptococcus bovis JB1 strains; Tazania grass silage inoculated with 106 ufc/g Streptococcus bovis JB1 with 10% wheat meal; Tanzania grass silage inoculated with 106 ufc/g Streptococcus bovis HC5 strains; Tanzania grass silage inoculated with 106 ufc/g Streptococcus bovis HC5 with 10% wheat meal. This experiment was conducted at the Department of Animal Science, in the Federal University of Viçosa, located in Viçosa city, in the State of Minas Gerais. It was used a paddock of Panicim maximum grass cv. Tanzania already deployed, of approximately 0,5 ha. After the uniform cutting, at 10 cm from the ground level, it was made fertilization with 50 kg/ha of nitrogen and potassium in the form of ammonium sulfate and potassium chloride, respectively. The cutting and silage of Tanzania grass was made after 65 days of growth. It was used experimental silos with capacity of 10 liters, equipped with Bunsen valve and 3 kg of sand at the bottom for added retention of effluent. The results showed that the greatest number of populations of enterobacteria, fungi and yeasts in the control silage. The silages inoculated with Streptococcus bovis JB1 and HC5 added with wheat meal, in addition to having the smallest populations of enterobacteria, fungi and yeast, showed higher numbers of lactic acid bacteria (P<0,05), 9,81 and 9,87 log ufc/g, respectivaly. The pH and ammonia-N were lower (P<0,05) for treataments with Streptococcus bovis JB1 and HC5 added with wheat meal, respectively. These silages also showed higher (P<0,05) lactic acid, 6,977 and 6,881% DM, respectively, and the lowest values of acetic, propionic and butyric acids. The silage inoculated with Streptococcus bovis showed a higher content (P<0,05) of crude protein and higher recovery of dry matter and crude protein, and smallest losses (P<0,05) of gases and effluents. For silages inoculated with Streptococcus bovis JB1 and HC5, added wheat meal, it was recorded higher values of soluble fraction “a” 32,76 and 32,17%, and to the degradability of dry matter and crude protein, 38,28 and 37,89%, respectively. Given the variables evaluated, there was a similarity of positive responses between the Streptococcus bovis JB1 and Streptococcus HC5, and the addition of wheat meal enhanced the effectiveness of microbial additve, and choosing between them depends on the cost of production.